Neutral sphingomyelinases control extracellular vesicles budding from the plasma membrane - Menck, Kerstin; Worst, Thomas; Boutros, Michael (Journal of extracellular vesicles, 2017)
Extracellular vesicles (EVs) are membrane particles secreted from cells into all body fluids. Several EV populations exist differing in size and cellular origin. Using differential centrifugation EVs pelleting at 14,000 g (“microvesicles” (MV)) and 100,000 g (“exosomes”) are distinguishable by protein markers. Neutral sphingomyelinase (nSMase) inhibition has been shown to inhibit exosome release from cells and has since been used to study their functional implications. How nSMases (also known as SMPD2 and SMPD3) affect the basal secretion of MVs is unclear. Here we investigated how SMPD2/3 impact both EV populations. SMPD2/3 inhibition by GW4869 or RNAi decreases secretion of exosomes, but also increases secretion of MVs from the plasma membrane. Both populations differ significantly in metabolite composition and Wnt proteins are specifically loaded onto MVs under these conditions. Taken together, our data reveal a novel regulatory function of SMPD2/3 in vesicle budding from the plasma membrane and clearly suggest that - despite the different vesicle biogenesis - the routes of vesicular export are adaptable.